Improving Students Comprehension of Present Continuous Tense through “NCT 127 JCC” with English Subtitles - Faishal Juliyanto; Lidiyatul Izzah; Diana Dewi (English Language in Focus (ELIF), 2023)
The goal of this study was to see if Johnny's Communication Center (JCC) with English subtitles could improve students' understanding of the present continuous tense. This study used a quantitative approach using a pre-experimental design, with pre-test, post-test, and interviews providing as instruments. This study was carried out at SMPN 5 South Tangerang with class 8.6 as a sample of 30 students. The T-test was used to assess the data. The research revealed that the average pre-test score was 59.17 and the average post-test score was 83.50. The t-test result was 13.476, and the significant (2-tailed) value was 0.000, which is less than 0.05 (<0.05). And the table above also shows that the t-test value was (13.476) and the t-table value was (5.147), which means that the t-test value was higher than the t-table. With that, it can be concluded that NCT 127 "Johnny's Communication Center" by English Subtitle is effective to improve students' Simple Present Continuous Tense Comprehension.